2017
DOI: 10.4014/jmb.1707.07040
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin Protects Human Mesenchymal Stem Cells from Oxidative Stress-Induced Senescence and Apoptosis

Abstract: Mesenchymal stem cells (MSCs) have been suggested as a primary candidate for cell therapy applications because they have self-renewal and differentiation capabilities. Although they can be expanded in ex vivo system, clinical application of these cells is still limited because they survive poorly and undergo senescence or apoptosis when transplanted and exposed to environmental factors such as oxidative stress. Thus, reducing oxidative stress is expected to improve the efficacy of MSC therapy. The milk protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…Additional potential regulators: The AKT pathway plays an important role in the rejuvenation of features and functions of aged MSCs. This pathway can act via ERBB4/PI3K/AKT[ 112 ], lactoferrin/AKT[ 113 ], Vc/AKT/mTOR[ 114 ], and fucoidan/FAK-Akt-TWIST axes[ 115 ]. Administration of rapamycin, an inhibitor of the mTOR signaling pathway, raised the expression level of NANOG, postponed replicative arrest, and enhanced the lifespan increment of BM-MSCs[ 116 ].…”
Section: Cellular Rejuvenation Strategiesmentioning
confidence: 99%
“…Additional potential regulators: The AKT pathway plays an important role in the rejuvenation of features and functions of aged MSCs. This pathway can act via ERBB4/PI3K/AKT[ 112 ], lactoferrin/AKT[ 113 ], Vc/AKT/mTOR[ 114 ], and fucoidan/FAK-Akt-TWIST axes[ 115 ]. Administration of rapamycin, an inhibitor of the mTOR signaling pathway, raised the expression level of NANOG, postponed replicative arrest, and enhanced the lifespan increment of BM-MSCs[ 116 ].…”
Section: Cellular Rejuvenation Strategiesmentioning
confidence: 99%
“…Lactoferrin plays a role in iron homeostasis, anti-inflammation, and host defense against microbial infections. Recently, it has been shown that lactoferrin inhibits the production of intracellular ROS in human mesenchymal stem cells, which suggests a potential role of lactoferrin in the prevention of OS-related damage [ 58 ]. Several RCTs have explored the effectiveness of oral lactoferrin in the prevention of NEC in preterm neonates.…”
Section: Exploring the “Milky Way”: Reducing Oxidative Stress By Imentioning
confidence: 99%
“…Research has reported that cells suffering from apoptosis involve endoplasmic reticulum (ER) stress, mitochondrial dysfunction, and death receptors [ 9 , 10 ]. Furthermore, oxidative stress plays a crucial role in regulating cancer cell behavior, especially associated with cell apoptosis [ 11 ]. High ROS levels were reported to have damaged ER function, resulting in unfolded proteins accumulation and ER stress [ 12 ].…”
Section: Introductionmentioning
confidence: 99%